A chronic eyelid lesion in a child: multi-disciplinary approach to diagnosis, treatment and management of a highly atypical histiocytic lesion. (17th February 2022) - Ramgopal, Archana; Segal, Julia; Mukhtar, Sabrina; Yu, Jenny; Picarsic, Jennifer; Tersak, Jean M.; Allen, Steven W.
Abstract: Malignant histiocytic neoplasm with histiocytic sarcoma phenotype is a rare malignant neoplasm, distinguished by malignant cells with phenotypic characteristics of mature tissue histiocytes. Histiocytic sarcoma typically presents as a primary malignancy, although can also present as a secondary malignancy, and is rarely seen in the pediatric population. Due to the rarity of this condition, diagnosis of histiocytic sarcoma is difficult and considered a diagnosis of exclusion. We describe a unique case of a chronic upper eyelid lesion with biopsy findings of a highly atypical histiocytic neoplasm initially concerning for histiocytic sarcoma; however, after integration of clinical findings, non-progressive and quiescent molecular profile, concluded to be an atypical juvenile xanthogranuloma in a child treated with excision and observation alone. This report highlights the importance of an integrated team approach to diagnosis of unusual histiocytic neoplasms.